2019
DOI: 10.1155/2019/7452019
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Transplant Outcome Is Associated with Regulatory T Cell Population and Gene Expression Early after Transplantation

Abstract: Successful long-term kidney allograft survival with parallel reduction of complications resulting from prolonged immunosuppressive treatment is a goal in kidney transplantation. We studied the immune changes in cell phenotypes and gene expression induced by kidney transplantation. Our goal was to find a phenotypic and/or transcriptional pattern that might be considered prognostic for the kidney transplant outcome. The analysis was performed prospectively on 36 KTx recipients sampled during the first year and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 49 publications
1
28
1
Order By: Relevance
“…Unlike our findings; Krajewska, et al showed a negative correlation between the recipient age and Treg population following KT [1]. Donor/recipient age mismatch in our study is an inevitable confounding factor, since our pediatric population received only adult living renal graft based on national regulations.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Unlike our findings; Krajewska, et al showed a negative correlation between the recipient age and Treg population following KT [1]. Donor/recipient age mismatch in our study is an inevitable confounding factor, since our pediatric population received only adult living renal graft based on national regulations.…”
Section: Discussioncontrasting
confidence: 88%
“…Recipient's immune status/sensitization, quality of organ, and immunosuppressive treatment are some of the factors that determine graft function and survival after Kidney Transplantation (KT) [1]. Different strategies have been developed in a trial to induce graft tolerance that necessitate better understanding of basic tolerogenic mechanisms as well as the capital role that T cells play during transplant rejection [2].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we do not know what happens in the first days after treatment. This limitation also applies to other studies [ 34 ], where the first sample had a month after treatment. It is likely that the effect of thymoglobulin is only observable in the short term and that the subsequent homeostatic lymphoproliferation of BL makes it difficult to detect differences in samples collected several months after drug administration.…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that RTRs receiving thymoglobulin have a PTX reduction in the frequency of naive BL associated with a relative increase in memory BL levels; however, when comparing BL levels between RTR with and without thymoglobulin, we did not obtain statistically significant differences. Although Zand et al [ 11 ] showed the in vitro anti-B effect of thymoglobulin by activating apoptotic pathways, several studies suggest a small in vivo effect on BL, even at high concentrations [ 34 ]. Gurkan et al [ 35 ] observed no differences in the absolute levels of BL of RTR treated with thymoglobulin.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Indeed, markers for the activation of CD8 + T cells can be detected in the peripheral blood isolated from kidney-transplant recipients (KTRs); especially, CD8 + T cell subsets belonging to the terminally-differentiated effector-cell state are known to be involved in the process of allograft rejection. [2][3][4][5] In contrast, CD8 + T cell subtypes that display a naïve cell state can be involved in an "anti-rejection" process by regulation of effector T cells. [6][7][8] Therefore, it is possible that the dynamics of CD8 + T subsets in the peripheral blood can show a significant change according to "rejection" and "stable" state; hence it has been proposed that monitoring of CD8 + T cells subsets may be useful for detecting acute allograft rejection.…”
Section: Introductionmentioning
confidence: 99%